Complete bandgap switching in photonic opals - Aryal, D.P.; K. L. Tsakmakidis; Hess, O. (New Journal of Physics, 2009)
A comprehensive theoretical study of the optical properties and switching competence of double-shell photonic crystals (DSPC) and doubleinverse-opal photonic crystals (DIOPC) is presented. Our analysis reveals that a DIOPC structure with a silicon (Si) background exhibits a complete photonic bandgap (PBG), which can be completely switched on and off by moving the core spheres inside the air pores of the inverse opal. We show that the size of this switchable PBG assumes a value of 3.78% upon judicious structural optimization, while its existence is almost independent of the radii of the interconnecting cylinders, whose sizes are difficult to control during the fabrication process. The Si-based DIOPC may thus offer a novel and practical route to complete PBG switching and optical functionality.